Achieving coordination of decentralized fisheries governance through collaborative arrangements: A case study of the Sian Ka'an Biosphere Reserve in Mexico. (July 2020) - Méndez-Medina, Crisol; Schmook, Birgit; Basurto, Xavier; Fulton, Stuart; Espinoza-Tenorio, Alejandro
Abstract: Decentralization of fisheries management in Mexico has created overlapping state agencies without clearly defined responsibilities. This has generated a management dilemma for national fisheries enforcement, due to ambiguity in implementation and legislation among agencies. Through a case study in the Sian Ka'an Biosphere Reserve, in the Yucatan Peninsula, we explore how local actors have addressed problems resulting from the implementation of these decentralized policies. We focus on local Community Surveillance Committees to understand how cooperation occurs at the local level to enforce fisheries regulations. Through a systematic review of fisheries policies in Mexico, we describe the political context to understand the implications of decentralization. The first author conducted ethnographic fieldwork from 2013 to 2017 in three fishing communities and attended meetings with actors involved in local fisheries management. As part of fieldwork, 42 in-depth interviews with fishers and representatives from state agencies were conducted. Using a polycentric approach, we look beyond the performance of individual fishing cooperatives to focus on the relationships among governance actors. We found factors strengthening the Sian Ka'an surveillance system are local actors' capacity to create rules, their relative autonomy from the government, and the existence of more than one decision-making center. We highlight that ambiguity in the implementation of decentralization also enabled local actors to be innovative and fill gaps in the national fisheries policies enforcement system, through diverse configurations of institutional arrangements. In this case study, those arrangements are the result of a constant process of social innovation and improvement in the fishery's organization.